Floodplain-channel complex of small river: assessment of current state, optimization measures - Kovalchuk, I.; Mykytchyn, O.; Andreychuk, Y.; Ivanov, E. (Land Management, Cadastre and Land Monitoring, 2017)
The article describes main methodological principles of geoecological assessment of riverbed-floodplain complex condition of one of the small rivers in Ukrainian Carpathians. According to our long-term field, cartographic, laboratory and remote sensing research, division of riverbed into homogeneous geoecological segments was made, as well as their standardization in accordance to the trends of unfavorable processes. Main reasons for deterioration of quality characteristics of channel-floodplain river complex were outlined; the role of natural and anthropogenic factors in deterioration of geoecological condition of the river and its floodplain complex was analyzed.Based on the assessment results it is possible to state that the condition of study segments of the Berezhnytsya river flood-plain and stream-way complex was marked as “excellent”, “good” and “satisfactory”. “Unsatisfactory” and “catastrophic” river and flood-plain condition has not been detected yet, although within Dashava urban settlement the river area condition is close to the “satisfactory” grade. The best situation is at the river head as human impact is minimized here and natural vegetation is preserved. Downstream we trace the tendency of condition worsening as anthropogenic load on the basin system and flood-plain and stream-way complex increases. Its negative impact is balanced by large forests, thus in segments limited by Banya Lysovytska village and Lotatnyky village the river and flood-plain condition is rated as “good”. So, downstream from the named village the value of such an important natural barrier as forest is reducing and anthropogenic load on the river significantly increases. The latter manifests in an intensive agricultural reclamation and housing development of flood-plains.Since degradation processes are rapidly developing over a considerable part of the Berezhnytsya river, negative changes are visible and only the study area, located close to the river head, is in almost optimal condition, a set of urgent measures to stop destructive for the river and its ecosystem processes, to rehabilitate the river and to preserve its resources should be made. Primary measures to improve the river condition should be: to clean off the stream-way and bank-line protective zone from domestic garbage and natural waste; to comply with behaviour requirements in respect of the bank-line protective zone and setting its limits; to fix eroded banks; to limit alluvium extracting from the bed and banks; to organize watering sites for animals; to provide better treatment of wastewater at municipal wastewater treatment plants located in Morshyn city and Dashava village, industrial effluents of Dashava production office of underground gas storage, Dashava composites plant, and Dashava construction materials plant management through their renovation; to reduce possibilities of getting water contaminated with the toxic waste from toxic waste landfill “Shkiryanyk”, into the river and to ensure the oil pipelines crosses the stream-way under the due protection. It is also important to reduce the regulation of a runoff because ponds are mainly lifeless and used for purposes other than intended ones. It is necessary to reduce the intensity of agricultural activity over the flood-plain lands. Key words: small river, floodplain-channel complex, human pressure, degradation, renaturalization.